Teachers’ Innovative Work Behavior Scale: Psychometric Properties of the Greek Version and Measurement Invariance across Genders - Angelos Gkontelos; Julie Vaiopoulou; Dimitrios Stamovlasis (Social Sciences, 2022)
Innovation refers to the implementation of creative ideas into practice. In that sense, innovative work behavior (IWB) is a type of behavior and a multidimensional construct that involves four factors: the generation, promotion, realization, and sustainability of new ideas for the whole organizations’ benefit. Thus, the development of instruments for measuring and singling IWB is an interesting and necessary endeavor. The present study appraises the psychometric properties of the Greek version of the innovative work behavior scale (IWBS-G), a 44-item self-reported instrument, using data collected from two studies with in-service teachers. In the first study dataset (N = 485), exploratory factor analysis was applied, which, by implementing scree plot with parallel analysis, revealed the dimensionality of four factors, namely: Idea Generation (IG), Idea Promotion (IP), Idea Realization (IR), and Idea Sustainability (IS). The corresponding reliability measures using Cronbach’s alpha and McDonald’s omega ranged between 0.917 and 0.944. In the second study dataset (N = 964), confirmatory factor analysis validated a sufficient fit of the measurement model [χ2 = 396.85, df = 203, p < 0.001; CFI = 0.995; TLI = 0.994; RMSEA = 0.031], while the corresponding internal consistency measures ranged between 0.814 and 0.914. Furthermore, measurement invariance was conducted, which demonstrated insignificant differences between genders. Discussion on the significance of innovative work behavior and the potential implementation of the IWBS instrument in educational research is provided.